2021
DOI: 10.1371/journal.pone.0261468
|View full text |Cite|
|
Sign up to set email alerts
|

Plant growth promoting rhizobacteria improve growth and yield related attributes of chili under low nitrogen availability

Abstract: Nitrogen (N) is a macronutrient desired by crop plants in large quantities. However, hiking fertilizer prices need alternative N sources for reducing its requirements through appropriate management practices. Plant growth promoting rhizobacteria (PGPR) are well-known for their role in lowering N requirements of crop plants. This study assessed the impact of PGPR inoculation on growth, allometry and biochemical traits of chili under different N doses. Two PGPR, i.e., Azospirillum ‘Er-20’ (nitrogen fixing) and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In similar studies [26], using Bacillus velezensis as inoculant of C. sativus, it was observed that the host plant modifies the root structure, which improves water and nutrient uptake, promoting a higher photosynthetic rate. It has been suggested that the modification of the root structure of a cucumber plant is related to the phytohormone indoleacetic acid (IAA) produced by S. meliloti, A. radioresistens, and P. paralactis [11,14,27]. In addition, it has been reported that S. meliloti and A. radioresistens possess the ability to fix nitrogen and solubilize phosphate, resulting in an increase on the number of late-stage roots and root hairs, since these elements are essential for the plant to increase photosynthetic pigments and proteins, which improves photosynthetic activity and rate, having a positive effect on plant development and a greater accumulation of biomass [28,29].Furthermore, it has been pointed out that IAA is associated with cell division and differentiation, which improves the structure of the root system [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In similar studies [26], using Bacillus velezensis as inoculant of C. sativus, it was observed that the host plant modifies the root structure, which improves water and nutrient uptake, promoting a higher photosynthetic rate. It has been suggested that the modification of the root structure of a cucumber plant is related to the phytohormone indoleacetic acid (IAA) produced by S. meliloti, A. radioresistens, and P. paralactis [11,14,27]. In addition, it has been reported that S. meliloti and A. radioresistens possess the ability to fix nitrogen and solubilize phosphate, resulting in an increase on the number of late-stage roots and root hairs, since these elements are essential for the plant to increase photosynthetic pigments and proteins, which improves photosynthetic activity and rate, having a positive effect on plant development and a greater accumulation of biomass [28,29].Furthermore, it has been pointed out that IAA is associated with cell division and differentiation, which improves the structure of the root system [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Plant growth-promoting rhizobacteria (PGPR) are a microorganism group able to increase the shoot and root length, improve water and nutrient absorption, and improve fruit quality and productivity in plants [13]. Undoubtedly, among the promoting mechanisms the production of phytohormone (auxin and cytokinins), volatile compounds, siderophores, atmospheric nitrogen fixation processes, and solubilized phosphate are the most important [12,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms (bacteria and fungi) present in the rhizosphere soil of plants play a significant role in the whole plant growth process ( Bukhat et al, 2020 ). Among these, plant growth-promoting rhizobacteria (PGPR) can promote the plant growth by various direct or indirect mechanisms, such as nitrogen fixation ( Raza et al, 2021 ), phosphate solubilization ( Sahu et al, 2022 ), siderophore production ( Braud et al, 2009 ; Ghazy and El-Nahrawy, 2021 ), heavy metal resistance ( Ma et al, 2016 ; Bennis et al, 2022 ), indole compound production ( Zahir et al, 2010 ), biocontrol ( Hosseini et al, 2021 ), and stress responses, including 1-aminocyclopropane-1-carboxylate (ACC) deaminase production ( Gupta et al, 2021 ), drought tolerance ( Mansour et al, 2021 ), and halotolerance ( Wang et al, 2022 ). In the past few decades, many studies on the screening and identification of these bacteria have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Stenotrophomonas malthopilia KJKB5.4, Stenotrophomonas pavanii LMTSA5.4, Bacillus cereus AJ34 and Alcaligenes faecalis AJ14 have rhizobacterial antibiosis to against Curvularia lunata by producing antibiotic compounds and increasing plant growth ( Rahma et al, 2021 ). The inoculation of Azospirillum Er-20 and Agrobacterium Ca-18 significantly improved the growth and yield of pepper, and had the potential to lower 25% N requirement for chili by nitrogen fixing and phosphorous solubilizing ( Raza et al, 2021 ). Xu et al (2022) found that the PGPR ( Tsukamurella tyrosinosolvens P9 and Burkholderia pyrrocinia P10) inoculations enhanced the photosynthetic performance, activated the antioxidant defense system, and decreased the ROS level of peanut plants, which alleviated the salt-induced cell damage and enhanced the salt tolerance and growth of peanut.…”
Section: Introductionmentioning
confidence: 99%